Facile Synthesis of 5-Bromo-N-Alkylthiophene-2-Sulfonamides and Its Activities Against Clinically Isolated New Delhi Metallo-β-Lactamase Producing Klebsiella pneumoniae ST147 - Noreen M; Bilal M; Usman Qamar M; Rasool N; Mahmood A; Umar Din S; Ali Shah T; Bin Jardan YA; Bourhia M; Ouahmane L (Infection and Drug Resistance, 2024)
Mnaza Noreen,1 Muhammad Bilal,1,2 Muhammad Usman Qamar,3,4 Nasir Rasool,1 Abid Mahmood,5 Sobia Umar Din,1 Tawaf Ali Shah,6 Yousef A Bin Jardan,7 Mohammed Bourhia,8 Lahcen Ouahmane9 1Department of Chemistry, Government College University Faisalabad, Faisalabad, 38000, Pakistan; 2School of Chemistry and Chemical Engineering, Shandong University, Jinan, 250100, People’s Republic of China; 3Institute of Microbiology, Faculty of Life Sciences, Government College, University Faisalabad, Faisalabad, 38000, Pakistan; 4Division of Infectious Disease and Department of Medicine, University of Geneva, Geneva, Switzerland; 5Department of Pharmaceutical Chemistry, Government College University Faisalabad, Faisalabad, 38000, Pakistan; 6College of Agriculture Engineering and Food Science, Shandong University of Technology, Zibo, 25500, People’s Republic of China; 7Department of Pharmaceutics, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 8Department of Chemistry and Biochemistry, Faculty of Medicine and Pharmacy, Ibn Zohr University, Laayoune, 70000, Morocco; 9Laboratory of Microbial Biotechnologies, Agrosciences and Environment (Biomage), Labeled Research Unit-CNRSTN° 4, Cadi Ayyad University, Marrakesh, 40000, MoroccoCorrespondence: Nasir Rasool; Mohammed Bourhia, Email nasirrasool@gcuf.edu.pk; m.bourhia@uiz.ac.maIntroduction: New Delhi Metallo-β-lactamase producing Klebsiella pneumoniae (NDM-1-KP) sequence type (ST) 147 poses a significant threat in clinical settings due to its evolution into two distinct directions: hypervirulence and carbapenem resistance. Hypervirulence results from a range of virulence factors, while carbapenem resistance stems from complex biological mechanisms. The NDM-1-KP ST147 clone has emerged as a recent addition to the family of successful clones within the species.Methods: In this study, we successfully synthesized 5-bromo-N-alkylthiophene-2-sulfonamides ( 3a-c) by reacting 5-bromothiophene-2-sulfonamide ( 1) with various alkyl bromides ( 2) using LiH. We also synthesized a series of compounds ( 4a-g) from compound ( 3b) using the Suzuki-Miyaura cross-coupling reaction with fair to good yields (56– 72%). Further, we screened the synthesized molecules against clinically isolated New Delhi Metallo-β-lactamase producing Klebsiella pneumoniae ST147. Subsequently, we conducted in-silico tests on compound 3b against a protein extracted from NDM-KP ST147 with PDB ID: 5N5I.Results: The compound ( 3b) with favourable drug candidate status, MIC of 0.39 μg/mL, and MBC of 0.78 μg/mL. This low molecular weight compound exhibited the highest potency against the resistant bacterial strains. The in-silico tests revealed that the compound 3b against a protein extracted from NDM-KP ST147 with PDB ID: 5N5I demonstrated H-bond and hydrophobic interactions.Conclusion: The 5-bromo-N-alkylthiophene-2-sulfonamides displayed antibacterial efficacy against New Delhi Metallo-β-lactamase producing Klebsiella pneumoniae ST147. After the in-vivo trial, this substance might offer an alternative therapeutic option. Keywords: NDM-1, antibacterial, drug resistance, Klebsiella pneumoniae, ST, sulfonamides